Linking the redox profile of metallocenyl-heteroaromatic derivatives to their in vitro biological activities - Manye, Remofilwe Eleanor (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.